The enigmatic dung beetle genus Stiptopodius Harold, 1871 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: new species descriptions from southern Africa - Daniel, Gimo M.; Deschodt, Christian M.; Davis, Adrian L.v.; Sole, Catherine L. (Zootaxa, 2020)
It is proposed that the genus Stiptopodius Harold, 1871 should be subdivided into two species groups based on the shape of the lateral edge of the pronotum. Three new species are described from southern Africa: Stiptopodius peringueyi Daniel & Deschodt, new species, Stiptopodius savuti Daniel & Deschodt, new species, and Stiptopodius muellerae Daniel & Deschodt, new species. Stiptopodius savuti new species is the first record of the genus from Botswana. A distribution map for the new taxa is provided. The identification key to the known species of Stiptopodius is updated.